Effect of b Value on Imaging Quality for Diffusion Tensor Imaging of the Spinal Cord at Ultrahigh Field Strength. - Shu-Sheng Bao; Can Zhao; Xing-Xing Bao; Jia-Sheng Rao (BioMed Research International, 2021)
Objective. To explore the optimal b value setting for diffusion tensor imaging of rats' spinal cord at ultrahigh field strength (7 T). Methods. Spinal cord diffusion tensor imaging data were collected from 14 rats (5 healthy, 9 spinal cord injured) with a series of b values (200, 300, 400, 500, 600, 700, 800, 900, and 1000 s/mm²) under the condition that other scanning parameters were consistent. The image quality (including image signal-to-noise ratio and image distortion degree) and data quality (i.e., the stability and consistency of the DTI-derived parameters, referred to as data stability and data consistency) were quantitatively evaluated. The min-max normalization method was used to process the calculation results of the four indicators. Finally, the image and data quality under each b value were synthesized to determine the optimal b value. Results. b = 200 s/mm² and b = 900 s/mm² ranked in the top two of the comprehensive evaluation, with the best image quality at b = 200 s/mm² and the best data quality at b = 900 s/mm². Conclusion. Considering the shortcomings of the ability of low b values to reflect the microstructure, b = 900 s/mm² can be used as the optimal b value for 7 T spinal cord diffusion tensor scanning.